Analysis of the corrosion rate and remaining life of the B3 waste transport roll-off tank composed of 316L stainless steel - Iwung Hari Retno; Wilarso; Che Wan Mohd Noor (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
Corrosion has eroded the shell and head of the roll-off tank used to carry B3 waste. This influence will effect on the functioning of the waste containment tanks, as well as the general safety of the public. The goal of this study was to examine the viability of employing a roll off tank by completing a visual inspection and engineering calculations using ASME VIII and API 510 standards to determine the corrosion rate and remaining life in the roll-off tank. This study employs a quantitative approach. Tank design data was acquired using SA-240/G316L material with an initial shell and head thickness of 6 mm and an actual thickness of 5.45 mm shell and 5.50 mm head. The corrosion rate and remaining life analysis yielded a Thickness Required shell value of 4.33 mm and a head value of 4.33 mm, with a shell and head Corrosion Rate value of 0.04 mpy, a Maximum Allowable Working Pressure (MAWP) value of shell and head of 0.63 Bar, and a shell and head remaining life value of 28 years and 30 years, respectively. It may be established that the roll-off tank is still operationally viable. Maintenance and testing regularly to improve roll-off tank performance